Study of Zwitterionic Homopolymer Polysulfobetaine and Gel Properties in Various Solutions of Different Anion Species and Cation Valences - Afan Hamzah; Daril Ridho Zuchrillah; Eva Oktavia Ningrum (IPTEK The Journal of Engineering, 2021)
Zwitterionic homopolymer polysulfobetaine (PBET) gels were synthesized using free radical polymerization. The effect of temperatures on adsorption behavior of the gel and transition temperature of the polymer in various solutions of LiCl, KCl, NaCl, Al(NO3)3, Zn(NO3)2, and NaNO3 were studied. The tendency of poly(BET)s transition temperature in Cl solutions very identical. All of poly(BET) solution resulted in Upper Critical Temperature (UCST). Its number increased along with the elevation of salt concentration. The number declined again when the concentration was too high. BET gel successfully adsorbed various ions with the amount of adsorption tendency of LiCl < NaCl < KCl.